Cytoarchitectonic Characterization and Functional Decoding of Four New Areas in the Human Lateral Orbitofrontal Cortex - Wojtasik, Magdalena; Bludau, Sebastian; Eickhoff, Simon B.; Mohlberg, Hartmut; Gerboga, Fatma; Caspers, Svenja; Amunts, Katrin (Frontiers in Neuroanatomy, 2020)
A comprehensive concept of the biological basis of reward, social and emotional behavior, and language requires a deeper understanding of the microstructure and connectivity of the underlying brain regions. Such understanding would provide insights into their role in functional networks, and form the anatomical basis of the functional segregation of this region as shown in recent in-vivo imaging studies. Here, we investigated the cytoarchitecture of the lateral orbitofrontal cortex (lateral OFC) in serial histological sections of ten human postmortem brains by image analysis and a statistically reproducible approach to detect borders between cortical areas. Profiles of the volume fraction of cell bodies were therefore extracted from digitized histological images, describing laminar changes from the layer I/layer II boundary to the white matter. As a result, four new areas, Fo4-7, were identified. Area Fo4 was mainly found in the anterior orbital gyrus, Fo5 anteriorly in the inferior frontal gyrus, Fo6 in the lateral orbital gyrus, and Fo7 in the lateral orbital sulcus. Areas differed in cortical thickness, abundance and size of pyramidal cells in layer III and degree of granularity in layer IV. A hierarchical cluster analysis was used to quantify cytoarchitectonic differences between them. The 3D-reconstructed areas were transformed to the single-subject template of the MNI, where probabilistic maps and a maximum probability map were calculated as part of the JuBrain Cytoarchitectonic Atlas. These maps served as reference data to study the functional properties of the areas using the BrainMap database. The type of behavioral tasks that activated them was analyzed to get first insights of co-activation patterns of the lateral OFC and its contribution to cognitive networks. Meta-analytic connectivity modeling showed that functional decoding revealed activation in gustatory perception in Fo4; reward and somesthetic perception in Fo5; semantic processing and pain perception in Fo6; and emotional processing and covert reading in Fo7. Together with existing maps of the JuBrain Cytoarchitectonic Atlas, the new maps can now be used as an open source reference for neuroimaging studies, allowing to further decode brain function.